Analysis of the provitability threshold for cabbage culture in conventional and ecological agriculture system: estimates 2019 / 2020 - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The prices of horticultural products fluctuate depending on a number of factors, such as perishability, storage possibilities, insufficient supply for a certain assortment, quality, etc., which can stimulate or reduce the incomes of agricultural producers. The paper aims to substantiate from a technical-economic point of view a system for elaborating production costs and estimating capitalization prices, the degree of profitability of the cabbage crop in the field, so that in the conditions of optimizing production structures, technologies applied and the financial support provided, to achieve high economic efficiency, in line with the performance of the European Union. The results of scientific research can have a positive influence on agricultural producers who can adapt their existing resources and capacities at the farm level to obtain high yields.
Keywords: Q12; Q14; Q57; 330; economic efficiency; profitability threshold; cabbage culture